PENGARUH METODE DISKUSI BERBANTUKAN MEDIA JOB SHEET TERHADAP HASIL MENJAHIT KEMEJA PRIA SISWA KELAS XI SMK NEGERI 1 KISARAN - Halida Hanim; Ratna Mahrida Purba (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACTThe study aims to know: 1) The learning outcomes of sewing shirt by using conventional learning method of students grade XI at SMK Negeri 1 Kisaran. 2) The learning outcomes of sewing shirt after using discussion method assisted by job sheet media of students grade XI SMK Negeri 1 Kisaran. 3) How far the influence of learning outcomes of sewing shirt after using discussion method assisted by job sheet media grade XI SMK Negeri 1 Kisaran. This study used a quasi experimental  method. The research design used was a post-test control group design. The population in this study were 62 students grade XI fashion at SMK Negeri 1 Kisaran. The samples were two classes randomly selected, each class consisted of 31 students. The first class used a discussion method  assisted  by job sheet media and the second class used a conventional learning method. The instrument of data collection was the observation sheet. Data were analyzed using t-test analysis technique. Based on the calculations that the level of trends in the learning outcomes of sewing shirt grade XI fashion at SMK Negeri 1 Kisaran for experimental class tend to be high at the 83,9 %. And the tendency level of sewing shirt learning result for the control class tend to be low at 87,1 %. The result of hypothesis test by using t-test was 44,04 > 1,67 at 5% significanct level. Therefore, it can be concluded that there is an effect of the application of discussion method assisted by job-sheet media on the learning outcomes of sewing shirt of students grade XI at SMK Negeri 1 Kisaran. Keywords: Discussion Method, Job Sheet Media and Male’s Shirt.